Outcomes of Endoscopic Resections of Large Laterally Spreading Colorectal Lesions in Inflammatory Bowel Disease: a Single United Kingdom Center Experience. Issue 6 (13th April 2018) - Gulati, Shraddha; Emmanuel, Andrew; Burt, Margaret; Dubois, Patrick; Hayee, Bu'Hussain; Haji, Amyn
Abstract: Background: The SCENIC consensus statement recommends endoscopic resection of all visible dysplasia in inflammatory bowel disease, but patients with large or complex lesions may still be advised to have colectomy. This article presents outcomes for large nonpolypoid resections associated with colitis at our institution. Methods: Data including demographics, clinical history, lesion characteristics, method of resection, and postresection surveillance were collected prospectively in patients with visible lesions within colitic mucosa from January 2011 to November 2016. Resection techniques included endoscopic mucosal resection, endoscopic submucosal dissection (ESD), and hybrid ESD. Surveillance with magnification chromoendoscopy was performed at 3 months, 1-year postresection, and annually thereafter. Results: Fifteen lesions satisfied the inclusion criteria in 15 patients. Mean lesion size was 48.3+/-21.7 (20–90) mm. All lesions were non-polypoid with distinct margins and no ulceration. 73% lesions were scarred of which 64% had undergone prior instrumentation. En bloc resection was achieved in n=6. Presumed endoscopic diagnosis was confirmed histopathologically in all resected lesions. One case of perforation and another with bleeding were both managed endoscopically. Median follow-up was 28 months (12–35) with no recurrence. Conclusion: This cohort series demonstrates that endoscopic resection of large non-polypoid lesions associated with colitis is feasible and safe using an array of resection methods supporting the role of advanced endoscopic therapeutics for the management of colitis associated dysplasia in a western tertiary endoscopic center.